Islamic Law Review of Judge Considerations in Agreeing to Marriage Dispensation (Case Study in The Klaten Religious Court) - Berlian Fajrul Falakh (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
This study explains the review of Islamic law on the Judge's considerations in determining marriage dispensation at the Klaten Religious Court. This research is library research by writing and clarifying data from various written sources at the Klaten Religious Court. Moreover, it is supported by field research in the form of interviews with judges and data collection of primary legal information for the Judge's considerations in providing marriage dispensation for the underage bride and groom couples and normative, juridical reviews regarding the issue of judges' considerations in determining marriage dispensations. This research shows that the legal considerations of marriage dispensation by the judges of the Klaten Religious Court are Law Number 1 of 1974 Article 7, paragraphs (1) and (2) concerning marriage. Whereas normatively, it is the fiqhiyah rule of